Peer Relationships at School - Soye, Emma (Bristol University Press, 2024)
Available Open Access digitally under CC-BY-NC-ND licence. This book draws on ethnographic research in two UK secondary schools, considering the shifting roles of migration status, language, ethnicity, religion and precarity in young people’s peer relationships. The book challenges culturalist understandings of social cohesion, highlighting the divisive impacts of neoliberalism, from pervasive temporariness and domestic abuse to technologization and neighbourhood violence. Using Martin Buber’s relational model, the book explores the interplay of ‘I-It’ boundary-making with reciprocal ‘I-Thou’ encounters, pointing to the creative power of these encounters to subvert, reimagine, and even transform social difference. The author provides a pragmatic and ultimately hopeful view of the dynamics of diversity in everyday life, offering valuable insights for social policy and practice.